The Application of a Case-Based Social Media-Assisted Teaching Method in Cariology Education：Comparative Study - Li Li; Xiaobin Liu; Zeyuan Chen; Liyuan Wang; Xiaoli Lian; Huiru Zou (JMIR Publications, 2021)
BackgroundCurrent cariology education based on the traditional teaching method faces a lot of challenges. Meanwhile, the COVID-19 pandemic caused an unprecedented disruption in medical education and health care systems worldwide. Innovation in the teaching mode of cariology education is required to change the situation. ObjectiveThe goal of the research was to evaluate the application effects of a case-based social media-assisted teaching method in cariology education. MethodsDental students of class 2019 were enrolled into the experimental group, while students of class 2018 served as control. A case-based social media-assisted teaching method was used in the experimental group, which included preclass activity via social media, additional discussion and practice process record in class, and questions and answers on the platform after class. The traditional teaching method, which consisted of conventional preparation before class, traditional lectures and demonstrations followed by students practice in class, and questions and answers step after class, was used in the control group. The teaching materials were the same in both groups. At the end of the program, students from both groups took cavity preparation skill evaluation tests. Questionnaires were tested on the case-based social media-assisted teaching group students anonymously. All data were analyzed using SPSS statistical software (version 22.0, IBM Corp). ResultsThe mean student cavity preparation skill evaluation scores was 82.51 (SD 6.82) in the experimental group and 77.19 (SD 5.98) in the control group (P<.05). The questionnaire response rate was 100%. Of those, 94.3% (100/106) of the students recommended the case-based social media-assisted teaching method in cariology education. The majority of the participants agreed that it helped them memorize the theoretical knowledge of cariology, facilitated in-depth discussion, improved their enthusiasm and initiative in learning, and enhanced the relationship between teachers and students (104/106, 98.1%). They also recognized that the classroom atmosphere was active (94/106, 88.7%). ConclusionsThe case-based social media-assisted teaching method was beneficial in terms of learning, as demonstrated by the statistically significant improvement of the cavity preparation skill evaluation scores and satisfaction from attending students. This method could be used to supplement the teaching of cariology.